An efficient route to unsymmetrical bis(azolium) salts: CCC-NHC pincer ligand complex precursors. Issue 16 (20th April 2017) - Box, Hannah K.; Howell, Tyler O.; Kennon, William E.; Burk, Griffin A.; Valle, Henry U.; Hollis, T. Keith
Abstract: The coupling of N -heterocyclic azoles (imidazoles, benzimidazoles, triazoles) to bromobenzenes (1, 2-; 1, 3-; or 1, 4) in a step-wise, sequential manner was accomplished by manipulation of reaction time and stoichiometry, which provided straight-forward access to unsymmetrical bis(azolium) salts in only three isolation steps from commercially-available starting materials. Eight mono(azole) substituted bromobenzenes, four mono(azolium)bromobenzene salts, twelve unsymmetrical bis(azole)benzenes, and fourteen unsymmetrical bis(azolium) salts, which are precursors for pincer ligand complexes, are reported. Graphical abstract: